CONSTRUCTION OF A DEMOCRATIC EDUCATION SYSTEM - Fathul Rahma; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Democracy will be the model of education in the future. A democratic educational system will produce graduates with social impact and the ability to participate in public decision-making. The reality, however, is not as anticipated. The current educational system is governed by a method of providing rather than digesting information. Furthermore, the relationship between teacher and student is founded on dominance rather than collaboration; the instructor controls the pupils. As a result, it is necessary to restructure and realign the educational system in order to build democratic education. At the very least, there are four elements to it: 1. Shift education administration from centralization to decentralization; 2. Shift education curriculum from theoretic to problem-oriented; 3. Use a constructivist method to teach subjects that are based on real-world problems experienced by students. 3. Treating kids like subjects rather than objects. 4. The teacher is a facilitator and motivator rather than a leader.